Empowering youth sport and acculturation: Examining the hosts' perspective in Greek adolescents. (May 2017) - Morela, Eleftheria; Hatzigeorgiadis, Antonis; Sanchez, Xavier; Papaioannou, Athanasios; Elbe, Anne-Marie
Abstract: Objectives: Research on the role of sport as a context for the acculturation of young migrants has mainly focused on migrant populations. Considering that acculturation is a two-way process involving both the migrant and the host populations, research investigating the perspective of the hosts will enhance our understanding of the acculturation process. The purpose of the present study was to explore acculturation attitudes and perceptions of adolescents from the host population as a function of sport participation. Furthermore, for those adolescents participating in sport, the role of the sport motivational climate and its relation to acculturation attitudes was investigated. Design and Method: A cross-sectional quantitative design was adopted. Participants were 626 (316 girls) Greek, high school students (13.88 ± 1.01 years of age). Among them, 271 (92 girls) were athletes competing in individual and team sports. While all participants completed measures of acculturation attitudes, the athletes additionally completed measures of motivational climate, basic need satisfaction, and controlling coaching behavior. Results: Athletes scored higher than non-athletes on attitudes towards multicultural contact. Analysis of structural models revealed that a motivational climate characterized by a mastery climate, supportive of the needs of autonomy, competence, and relatedness, was positively linked to attitudes favoring migrants' maintenance of their culture and development of interaction with the host culture, whereas a motivational climate characterized by a performance climate and controlling coaching behavior was negatively linked to such attitudes. Conclusion: These findings provide useful insights concerning the perspectives of the host population regarding migrants' acculturation and the role motivational climate play in promoting integration. Highlights: Athletes showed more accepting attitudes towards multicultural contact than non-athletes. Empowering athletic climate was positively linked to multiculturalism attitudes. Disempowering athletic climate was negatively linked to multiculturalism attitudes. Youth sports may induce desirable integration outcomes when the sport environment is appropriate.